The brazilian judicial system and the definition of the best interest of the child - Moraes, Maria Lygia Quartim de (FCL-UNESP Laboratório Editorial, 2014)
Few institutions have undergone such profound changes as the Brazilian family. The changes affect both the institution of marriage and the relations of power and responsibility between mothers and fathers. Recent data confirms that family size has decreased as well as divorce and consensual unions have increased over time. It is necessary to highlight that changes in family laws have followed changes in real life as shown in the 1982 Constitution and the 1990 Statute of Children and Adolescents. Thus, the consolidation of new legal rights is accompanied by the increasing judicialization of social relations. In other words, the judiciary has become the arbiter of relations between parents and children, bolstering decisions in the field of human sciences. This paper presents some considerations on the implications of the judicialization of family relationships.